Jonn Colet and the Hierarchies of the PS-Dionysius - Trapp, J. B. (Studies in church history, 1981)
John Colet, Dean of St Paul’s from 1504 or 1505 until his death at the age of 52 in 1519 was a man, according to the brief biography of him written a couple of years after his death by his friend Erasmus—it remains the best sketch of his character—whom neither the smiles of fortune (he was born well-to-do, and was early on the path of ecclesiastical preferment) nor the impulse of a far different natural bent (he was high-tempered, self-confessedly prone to incontinence and luxuriousness, to indulgence in sleep, to jests and raillery, was not even free from the taint of avarice) could divert from the pursuit of a gospel life. His defects he counteracted by philosophy and sacred studies, watching, fasting and prayer, in a life that was both chaste and charitable. His large patrimony went, in the first decade of the sixteenth century, to the foundation of St Paul’s School, ‘specially to increase knowledge and worshipping of god and our lorde Crist Jesu and good Cristen lyff and maners’. There a limited number were to be taught by a High Master and a Sur-Master, with a chaplain, who were to devote their whole time to the school. Delighting in the purity and simplicity of children, Colet saw that ‘a nation’s chief hope lay in having the rising generation trained in good principles.